2022
DOI: 10.3389/fmicb.2022.928877
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial biofilm colonization and succession in tropical marine waters are similar across different types of stone materials used in seawall construction

Abstract: Seawalls are important in protecting coastlines from currents, erosion, sea-level rise, and flooding. They are, however, associated with reduced biodiversity, due to their steep orientation, lack of microhabitats, and the materials used in their construction. Hence, there is considerable interest in modifying seawalls to enhance the settlement and diversity of marine organisms, as microbial biofilms play a critical role facilitating algal and invertebrate colonization. We assessed how different stone materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 64 publications
1
5
0
Order By: Relevance
“…Different concrete compositions showed different colonization patterns during the first weeks, but these differences tended to even out, suggesting a replacement of initially adhering microorganisms with more generic concrete colonizers, as also suggested by Ref. [39]. No special acid-producing genera were detected in the sessile populations, although calcium was removed from the concrete surfaces, indicating corrosion.…”
Section: Concrete In the Submerged Zonesupporting
confidence: 55%
See 2 more Smart Citations
“…Different concrete compositions showed different colonization patterns during the first weeks, but these differences tended to even out, suggesting a replacement of initially adhering microorganisms with more generic concrete colonizers, as also suggested by Ref. [39]. No special acid-producing genera were detected in the sessile populations, although calcium was removed from the concrete surfaces, indicating corrosion.…”
Section: Concrete In the Submerged Zonesupporting
confidence: 55%
“…Ref. [39], after a series of experiments to assess the effects of different stone substrata (including concrete) on marine biofilm formation, similarly concluded that the biofilms converged over time to a generic marine type and that the underlying substrata did not play a significant role in community composition. Where the substrata are similar, as in this case where they were all types of natural or artificial stone, this may be true, but there are certainly differences between the biofilm-formers on very different substrates in seawater, such as concrete and wood, for example [60].…”
Section: Microbial Adhesion and Biofilm Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Natanzi et al (2021) reported differences in the relative abundances of cyanobacteria, diatoms associated with different concrete mixtures after one month. Conversely, after a similar deployment time (31 days), Summers et al (2022) found no differences in microbial diversity among the same stone types tested in Hartanto et al (2022). Whilst it appears that surface properties may influence microbial communities early on, it appears that communities converge later in the ecological succession process.…”
Section: Wider Consideration Of Materials and Substrate Typesmentioning
confidence: 76%
“…-Consideration of greater number of materials (Becker et al, 2020;Hsiung et al, 2020;Schaefer et al, 2020Schaefer et al, , 2023Vivier et al, 2021a;Natanzi et al, 2021;Dauvin et al, 2022;Dodds et al, 2022;Hartanto et al, 2022;Lapinski et al, 2022;Summers et al, 2022).…”
Section: Greening Of Grey Infrastructure (Ggi) On Marine Artificial S...mentioning
confidence: 99%